In vitro inhibitory effects of thymol and quinones of Nigella sativa seeds on cyclooxygenase-1- and -2-catalyzed prostaglandin E2 biosyntheses - Marsik, Petr; Kokoska, Ladislav; Landa, Premysl; Nepovim, Ales; Soudek, Petr; Vanek, Tomas (Planta medica, 2005)
Dithymoquinone, thymohydroquinone, thymol and thymoquinone, compounds derived from N. sativa seeds, were investigated for their in vitro anti-inflammatory activities using cyclooxygenase-1 (COX-1) and -2 (COX-2) assays. Our results show that all substances tested possess significant inhibitory activity against at least one COX form at concentrations comparable to the active one of indomethacin. Thymol was the most active against COX-1 with an IC (50) value of 0.2 microM while thymohydroquinone and thymoquinone exhibited the strongest inhibitory effect on COX-2 with IC (50) values of 0.1 and 0.3 microM, respectively. Moreover, dithymoquinone and thymoquinone showed a limited COX-2-specific inhibition. We conclude that dithymoquinone, thymohydroquinone, thymol and thymoquinone can participate in the general anti-inflammatory activity of N. sativa and suggest that these agents should be further studied for possible use as non-steroidal anti-inflammatory drugs.
Keywords: vztah mezi dávkou a účinkem léčiva; thymol; Cyclooxygenase Inhibitors; Inhibitory Concentration 50; chinony; Cyclooxygenase 2; Seeds; semena rostlinná; rostlinné extrakty; Dinoprostone; cyklooxygenasy; lidé; Cyclooxygenase 2 Inhibitors; dinoproston; inhibitory cyklooxygenasy 2; inhibiční koncentrace 50; Phytotherapy; membránové proteiny; Nigella sativa; Thymol; Dose-Response Relationship, Drug; fytoterapie; cyklooxygenasa 2; cyklooxygenasa 1; inhibitory cyklooxygenasy; Quinones; Plant Extracts; Membrane Proteins; Prostaglandin-Endoperoxide Synthases; Cyclooxygenase 1; Humans